A retrospective cohort study: The retention in care of HIV positive pregnant and breastfeeding patients universally initiated on lifelong ART ('OptionB+') in the Klipfontein/Mitchells Plain substructure in Cape Town - Engelbrecht, Alida M (Department of Public Health and Family Medicine, 2016)
The implementation of 'Option B+' has increased uptake and access to antiretroviral (ART) care. However, growing concerns exist regarding retention, especially once vertical transmission risk ceases. Considering the importance of adherence to achieve virological suppression and avoid resistance research on retention is crucial. This study compares the retention of women initiated on 'Option B+' to that of women initiating ART for their own health. Additionally possible predictors of loss to follow-up (LTFU) were explored. Women initiating ART between 1 April and 31 August 2013 were allocated to either the pregnant (n=228) or non-pregnant (n=177) cohort. Retrospective review of electronic recordkeeping systems and patient folders measured retention up to 15 months after ART initiation. Demographic data was captured to explore predictors of LTFU. To avoid outcome bias with participants transferred out, analysis included a 'worst case' scenario assuming LTFU of all these participants and a 'best case' scenario assuming continued retention in care.